2017
DOI: 10.1021/acsphotonics.7b00310
|View full text |Cite
|
Sign up to set email alerts
|

Structural Protein-Based Whispering Gallery Mode Resonators

Abstract: Nature provides a set of solutions for photonic structures that are finely tuned, organically diverse, and optically efficient. Exquisite knowledge of structure−property relationships in proteins aids in the design of materials with desired properties for building devices with novel functionalities, which are difficult to achieve or previously unattainable.Here we report whispering-gallery-mode (WGM) microresonators fabricated entirely from semicrystalline structural proteins (i.e., squid ring teeth, SRT, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 39 publications
(66 reference statements)
0
21
0
Order By: Relevance
“…The amino acid sequence of proteins determines their secondary and tertiary structures; hence they provide a variety of structural conformations . Proteins can often self‐assemble in order to form natural materials with extraordinary properties such as extremely high durability or elasticity . Hence, designing new proteins using biotechnology tools has been an interest for materials scientists for modifying and assembling novel morphologies and molecular architectures .…”
Section: Protein‐based 2d Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid sequence of proteins determines their secondary and tertiary structures; hence they provide a variety of structural conformations . Proteins can often self‐assemble in order to form natural materials with extraordinary properties such as extremely high durability or elasticity . Hence, designing new proteins using biotechnology tools has been an interest for materials scientists for modifying and assembling novel morphologies and molecular architectures .…”
Section: Protein‐based 2d Nanocompositesmentioning
confidence: 99%
“…Proteins can often self‐assemble in order to form natural materials with extraordinary properties such as extremely high durability or elasticity . Hence, designing new proteins using biotechnology tools has been an interest for materials scientists for modifying and assembling novel morphologies and molecular architectures . The amino acid sequences of the proteins can be controlled to prescribe the alignment of 2D layers that form the substrate of composites, ultimately dictating different functional properties (e.g., mechanical, optical, electrical, and thermal).…”
Section: Protein‐based 2d Nanocompositesmentioning
confidence: 99%
“…Ordered domains like β-sheet structures provide mechanical strength (e.g., SRT and silk fibroin are β-sheet-rich structural proteins with modulus in the GPa range), while disordered domains provide elasticity and flexibility to the material (e.g., similar to disordered resilin in the wing tendon of insects) (Cheng et al, 2010; Guerette et al, 2013; Yarger et al, 2018). The secondary structure content does not only influence the mechanical properties of SRT-based materials, but also their thermal (Jung et al, 2017), conducting (Pena-Francesch et al, 2018b), and optical properties (Yilmaz et al, 2016, 2017). The morphology of disordered domains also plays an important role in defining the bulk properties of protein-based SRT materials.…”
Section: Squid Ring Teeth Based Fibers and Filmsmentioning
confidence: 99%
“…By combining the concept of biomimicry and theoretical foundations of block copolymers, these structural motifs have been exploited to design protein-based materials with remarkable new properties. Many reports have shown that these new materials can have interesting and useful mechanical, optical, and thermal properties [4][5][6][7][8][9][10][11]. Moreover, tandem repeat proteins govern the assembly of composites materials such as graphene oxide and MXenes (Ti3C2Tx) for 2D layered structures as well as self-healing characteristics of conducting polymers for applications in flexible electronics and biocompatible electronics [12][13][14].…”
Section: Introductionmentioning
confidence: 99%